Reactive nitrogen and oxygen species in anticoagulated blood of healthy sheep. (September 2013) - Nwose, Ezekiel Uba; Bwititi, Phillip Taderera; Chalada, Melissa Judith
Abstract : Background : Little or no study has been done to compare the indices of 'nitrosative' and 'oxidative' stresses, especially in terms of correlation and the possible differential effects of the chelating agents. Objective: This preliminary study investigated possible correlations between the indices of reactive nitrogen species (RNS) and reactive oxygen species (ROS) in blood, effect of anticoagulated-blood tubes, and impact of blood-clotting pathways. Methods: Thirty blood samples from sheep were collected into ethylenediamine tetraacetic acid (EDTA) and citrate tubes at the Berrima Veterinary Laboratory using their standard protocol. Nitrosative and oxidative stress indices were then measured and correlation analyses performed. Results: The ROS and RNS indices were weakly correlated (r > 0.2; p < 0.05) with each other from the EDTA sample, but not from citrated blood. None of the nitrosative or oxidative stress biomarkers was significantly associated with changes in the prothrombin time. The activated partial thromboplastin time showed statistically significant association with some oxidative stress indices (catalase and malondialdehyde), but with none of the nitrosative stress indices. Further, all measured parameters were higher in EDTA than in citrate blood (p < 0.0001). Conclusion: The choice of anticoagulated blood tube could affect the measures of nitrosative stress indices and may impact on the potential correlations between nitrosative versus oxidative stress biomarkers. Perhaps the suggestion that EDTA is better than citrate for hematological anticoagulant studies should be considered for nitrosative and oxidative stress studies.